La ciencia política a través de sus manuales: tendencias teóricas y perspectivas metodológicas. México y América Latina en perspectiva comparada (2020)
A review of the development of political science in Mexico and Latin America is carried out from the internal perspective of the history of science. Based on a selection of political science handbooks written and/or translated into Spanish, topics, paradigms, and methodologies that have dominated the discipline in various periods —from the early 20th century until the first decades of the 21st century— are comparatively analyzed. The scopes and objectives of a discipline, delimited by the scientific community which cultivates it, are contained in handbooks. This way, they become an essential object for understanding the sociology of political science. Four theoretical methodological trends are identified in the same number of periods: philosophical-institutionalist; legal-institutionalist; sociological-functionalist and Marxist; and finally, democratic-pluralistic. It is important to note that political science emerged with low independence from other disciplines. Currently, political science has its own paradigms and theories. It has incorporated new discussions as a reflex of historical-political changes in the region.